Evidence-based spatial design to improve clinical staff efficiency in obstetrical nursing units - Lu, Xiao-xuan (2018)
A growing number of people are beginning to pay attention to the healthcare environment design, not only to meet the needs of treating patients, but also to consider the psychological demands of clinical staff. Patient safety and quality of care all depend on creating an efficient and effective working environment for clinical staff. In China, some obstetric designs have prevented the space and rooms from reaching its maximum efficiency. In addition, some imperfect functions have reduced staff efficiency and causing social dissatisfaction. Relatively few studies have investigated the impact of the physical environment on staff. The study focused on the effect of the design of obstetrical nursing units on clinical staff efficiency to develop a high-quality and efficient healing environment. It presented a method that combined practical and theoretical to the investigation of the spatial and social attributes of obstetrical nursing units. Evidence-based design theory was used to investigate obstetrics in three hospitals including corridors, nurse stations, wards and physical environment, and interviews and questionnaires were also conducted to understand the needs of clinical staff. The layouts of nursing unit were simulated by measuring the spatial properties of the three floor plans based on space syntax theory. A comparative analysis of the results found that hospital design often needs to balance multiple constraints, for example, the balance between improving the efficiency of staff and protecting the patient privacy. The study proposed improvement recommendations for nursing units, and the methods that can be applied to environmental and behavioral studies in other researches. In addition to spatial layout design, architects need to consider other influencing factors, including the location and scale of the building, economic budget, and users’ psychology.